Indian contract & specific relief acts : Vol. I - Pollock, Frederick, 1845-1937.; Mulla, Dinshah Fardunji, Sir, 1868-1934.; Padia, R. G.; India; India (New Delhi : LexisNexis Butterworths, 2006)
Commentaries on Indian Contract Act, 1872 and Specific Relief Act, 1963
Keywords: India; India; Contracts -- India; Equitable remedies -- India